Nesterenkonia muleiensis sp. nov., a novel actinobacterium isolated from sap of Populus euphratica. Issue 3 (22nd January 2020) - Wang, Ruijun; Anwar, Nusratgul; Ding, Jinglin; Ye, Yanghui; Ren, Yanhu; Fu, Geyi; Chen, Can; Xu, Jinzhong; Wu, Min
Abstract : A novel, Gram-stain-positive, aerobic, non-endospore-forming, non-motile and rod-shaped bacterium designated RB2 T was isolated from sap of Populus euphratica collected in Mulei county, Xinjiang province, PR China. RB2 T was able to grow at 10–45 °C (optimum 35 °C), pH 6.0–12.0 (optimum 8.0) and with 0–12 % (w/v) NaCl (optimum 1 %). The genomic DNA G+C content was 63.5 % (from the genome sequence). The results of the chemotaxonomic analysis indicated that the predominant isoprenoid quinones were MK-8 and MK-9. The major fatty acids were anteiso-C15 : 0 and anteiso-C17 : 0 . The major polar lipids of RB2 T were diphosphatidylglycerol, phosphatidylglycerol, phosphatidylinositol and two glycolipids. The peptidoglycan type of RB2 T was A4 α, l -Lys–Gly–l -Glu. The results of the phylogenetic analysis, along with the phenotypic and chemotaxonomic characteristics, indicate that strain RB2 T represents a novel species of the genus Nesterenkonia, for which the name Nesterenkonia muleiensis sp. nov. is proposed. The type strain is RB2 T (=MCCC 1K03528 T =KCTC 49017 T ).